Religious revival or disqualification on post-globalized social reality? US case & its troubles (Journal of the Sociology and Theory of Religion, 2018)
This critical and comparative study combines Religious Sciences, Sociology, Philosophy & Theology (with other Social Sciences and Liberal Arts linked), to offer a holistic view on the role of religion in a post-globalized social reality. It addresses the state of the main social spheres, including religion, with an ontological, epistemological and axiological examination, as well as removing veils of confusion about it. This paper is focused on American/US social reality and its roots, where historical & historiographically the religion has enjoyed great power and presence, but now it is a fuzzy issue on troubles.
Keywords: Religious Revival, Religious Disqualification, Post-Globalized Social Reality, The United States of America (USA/US), Social Spheres, Identity Issue.